Expression of p53 protein in psoriasis - Baran, Wojciech (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2005)
Introduction: Psoriasis is characterized by hyperproliferation and abnormal differentiation of keratinocytes, by the presence of inflammatory cell infiltrate in both the dermis and the epidermis and by alterations of capillaries. p53 protein is an important transcription factor which plays a central role in cell cycle regulation mechanisms and cell proliferation control. Objectives: This study was performed to identify the expression and localization of p53 protein in lesional and non-lesional skin samples taken from psoriatic patients in comparison with healthy controls. Material and methods: Sections of psoriatic lesional and non-lesional skin (n=18) were examined. A control group (n=10) of healthy volunteers with no personal and family history of psoriasis was also examined. The expression of p53 was demonstrated using the avidin - biotin complex immunoperoxidase method and themonoclonal antibody D07. The count and localization of cells with stained nuclei was evaluated using a light microscope in 10 fields for every skin biopsy. Results: In lesional psoriatic skin the count of p53 positive cells was significantly higher than in the skin samples taken from healthy individuals (p<0.01) and non-lesional skin taken from psoriatic patients (p=0.02). No significant difference between non-lesional psoriatic skin and normal skin was observed (p=0.1). A strong positive correlation between mean count and mean per cent of p53 positive cells was found (p<0.0001). P53 positive cells were located most commonly in the basal layer of the epidermis of both healthy skin and non-lesional psoriatic skin. In lesional psoriatic skin p53 positive cells were present in all layers of the epidermis. Conclusion: P53 protein appears to be an important factor in the pathogenesis of psoriasis.
Keywords: Beljakovina p53; dermatologija; histologija; Immunohistochemistry; Imunohistokemija; Pathology; Protein P53; Psoriasis; Psoriaza